An Initiative Report on Hospitalized Pulmonary TB Patients Co-Infected by SARS-CoV-2 during the COVID-19 Pandemic from Tertiary Referral Hospitals in Surabaya - Effendy, Lyndia; Mertaniasih, Ni Made; Soedarsono, Soedarsono; Endraswari, Pepy (Institute of Topical Disease Universitas Airlangga, 2023)
The enduring effect of SARS-CoV-2 pandemic has been experienced throughout the past and ongoing three years. Incidences of SARS-CoV-2 co-infected tuberculosis patients were reported globally, including in Italy and several European countries and resulted in a more complicated disease with severe clinical features and poorer clinical outcomes. To effectively manage this co-infection, it is important to be informed of the prevalence and characteristics of an acute SARS-CoV-2 co-infection on TB and determining factors of severity. Therefore, early warning signs can be recognized, monitored closely and managed. This retrospective study, carried out on hospitalized TB patients in Dr. Soetomo Hospital and Universitas Airlangga Hospital, Surabaya, Indonesia, used medical records from March 2020 to December 2022. Samples were from inpatients with a molecularly-Gene Xpert MTB/Rif-confirmed tuberculosis, and currently experienced respiratory and fever symptoms that resembles the symptoms of SARS-CoV-2 infection or exacerbation of tuberculosis. They are then screened and examined using a molecular diagnostic test, with real-time RT-PCR for SARS-CoV-2. A total of 54 (0.7%) patients had TB-SARS-CoV-2 co-infection among 7,786 suspected to have TB, of which 35 had Rifampicin Sensitive (TB-RS), while 19 had TB Rifampicin Resistant (TB-RR) co-infected with SARS-CoV-2. The remaining 2,586 suspected TB patients had only MTB, based on the detection methods of X-pert MTB/RIF, but with negative RT-PCR of SARS-CoV-2. The clinical severity and mortality of TB-SARS-CoV2 co-infected patients were significantly associated with the number of co-morbidities (p=0.0156), and serum haemoglobin levels (p=0.0672), in which p value < 0.05 is considered significant.